Peran Organisasi Daerah dalam Pengembangan Diri Santri (Studi Analisis Organisasi Iksandalika di Pondok Pesantren Annuqayah Lubangsa Selatan) - Moh. Ali Makki (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
Self-development is very urgent to add broad insights of all aspects. Not just in theory, but it should bring into an action as well. Recognizing the importance of self-development, the researcher identified the problem of weak self-development among santri of Pondok Pesantren Annuqayah Lubangsa Selatan, with the case of less-creativity among santri as well as their dependency on doing things. This research is intended to reveal three things: First, the role of the Iksandalika organisation in the self-development of santri, Second, the driving factors and barriers of the Iksandalika organisation in the self-development of santri, Third, the solution to the organizational barrier factors in the self-development of santri. To analyse this, the author uses Abraham Maslow's theory of the hierarchy of needs, which includes physiological needs, security, social, appreciation, and self-actualisation. As for the research methodology, the author uses a case approach, utilizing observation, interviews, and documentation for data collection. After conducting an in-depth analysis, this research identifies three roles of the Iksandalika organisation in developing santri at Pondok Pesantren Annuqayah Lubangsa Selatan including, first, the role of the Iksandalika organisation as an organisational platform, second, the role of the Iksandalika organisation as a catalyst or motivator, third, the role of the Iksandalika organisation as a form of santri guidance. The driving factors include: the enthusiasm of students in the organisation, intelligence factors, and environmental factors. While the barrier factors are: the lack of awareness of santri, not feeling at home, insufficient support from the closest associates. The solution to overcome these barrier factors is to understand the character of each student, provide socialisation about the urgency of self-development, provide motivation to the santri.